Soil Microbial Resource Limitations and Community Assembly Along a Camellia oleifera Plantation Chronosequence - Qiao, Hang; Chen, Longsheng; Hu, Yajun; Deng, Chenghua; Sun, Qi; Deng, Shaohong; Chen, Xiangbi; Mei, Li; Wu, Jinshui; Su, Yirong (Frontiers in Microbiology, 2021)
Understanding soil microbial element limitation and its relation with the microbial community can help in elucidating the soil fertility status and improving nutrient management of planted forest ecosystems. The stand age of a planted forest determines the aboveground forest biomass and structure and underground microbial function and diversity. In this study, we investigated 30 plantations of Camellia oleifera distributed across the subtropical region of China that we classified into four stand ages (planted <9 years, 9–20 years, 21–60 years, and >60 years age). Enzymatic stoichiometry analysis showed that microbial metabolism in the forests was mainly limited by C and P. P limitation significantly decreased and C limitation slightly increased along the stand age gradient. The alpha diversity of the soil microbiota remained steady along stand age, while microbial communities gradually converged from scattered to clustered, which was accompanied by a decrease in network complexity. The soil bacterial community assembly shifted from stochastic to deterministic processes, which probably contributed to a decrease in soil pH along stand age. Our findings emphasize that the stand age regulated the soil microbial metabolism limitation and community assembly, which provides new insight into the improvement of C and P management in subtropical planted forest.